Determinants of Adoption of Improved Maize Varieties and Chemical Fertilizers in Mozambique - Eunice Cavane; Cynthia Donavan (Journal of International Agricultural and Extension Education, 2011)
In Mozambique, adoption of improved maize seed and chemical fertilizers is still limited. This study assessed farmers’ attitudes towards hybrid maize SC513, Nitrogenous (N) Phosphorous (P) Potassium (K), (NPK 12-24-12) and urea fertilizers in highlands and lowlands of the Manica District. The study determined the influence of farmers’ characteristics, attitudes, sources of information, and agro-ecological conditions on adoption of these technologies during 1995 through 2005. A questionnaire was administered during April and May 2006 with a randomly selected sample of 293 households. In general, farmers held positive attitudes towards improved maize varieties and chemical fertilizers, but the strength of attitudes towards fertilizers, in particular, varied by source of information. Farmers who learned about fertilizers from extension had stronger positive attitudes than farmers who learned about fertilizers from neighbors, although with hybrid seeds adoption, there was no significant difference between key sources. Overall, the number of farmers using SC513 was higher than the number of farmers using NPK and urea. Farmers’ decision to adopt SC513 was positively associated with agro-ecological conditions, knowledge, production traits and marketability of the maize. Agro-ecological conditions, knowledge of fertilizer application, and extension contact influenced adoption of chemical fertilizers. The results differentiate a simpler process of adoption of new seed from a more complex process of adoption of fertilizers which demands greater knowledge of timing and soils as well as basic computational skills. Factors determining adoption of hybrid maize varieties and chemical fertilizers should be considered when designing extension programs for these technologies.
Keywords: Adoption; attitudes; chemical fertilizer; extension; improved maize varieties